Analisis Pengaruh Holding Time terhadap Sifat Mekanis dan Struktur Mikro pada Proses Induction Tempering Batang Piston Baja SCM 420 H - Budiarto, Budiarto; Turnip, Kimar (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2018)
Selection of materials connecting rod for a component or structure usually involves several aspects, there are aspects of specific strength, stiffness, lightweight, noncorrosive materials and resistance or age. In the manufacturing process connecting rod always give heat treatment such as Normalizing, Carburizing, and Induction Tempering. In the process, Induction Tempering has a big problem in hardness after the process, not stable and liable to over from standard. Process condition of tempering induction temperature in 650 700 C at 1 atm pressure, & holding time variation at 5, 10, 15, and 20 seconds. Kind of tests such as bending test, magna-flux, hardness, and structure micro. Bending test report fiber flow is straight, not broke because not found micro crack portension at body connecting rod. Hardness test result min point 23 HRC and max point 39,2 HRC base on standard range 25 44 HRC. The results of surface morphological observation show that the martensite phase causes hardness value to increase.